The Archaeology of Digital Abandonment: Online Sustainability and Archaeological Sites. Issue 1 (2nd May 2014) - Law, Matt; Morgan, Colleen
After 15 years of hosting millions of user-built webpages, in April 2009 Yahoo! announced that they would be shutting down their United States Geocities webpages. Geocities was once the most common hosting service for low-cost personal webpages, including hundreds of public outreach sites about archaeology. Were the webpages moved to another hosting site, archived, or just abandoned? We tracked and recorded the fate of 88 of these webpages, eventually sending a survey to the webmasters asking them a range of questions. While we received relatively few responses, the answers to the questions were illuminating. Much of the current digital outreach performed all over the world relies on 'free' services such as Twitter, Flickr, Wordpress, Google Pages, or Facebook to host their content. What can the fate of archaeological content on Geocities pages tell us about the benefits and risks of using commercial infrastructure for archaeological outreach? We propose that sorting through the digital wreckage of past outreach efforts helps us to evaluate the eventual fate of the archaeological presence online.